Fractional flow reserve in patients with reduced ejection fraction. (16th August 2019) - Di Gioia, Giuseppe; De Bruyne, Bernard; Pellicano, Mariano; Bartunek, Jozef; Colaiori, Iginio; Fiordelisi, Antonella; Canciello, Grazia; Xaplanteris, Panagiotis; Fournier, Stephane; Katbeh, Asim; Franco, Danilo; Kodeboina, Monika; et al.
Abstract: Aims: Fractional flow reserve (FFR) has never been investigated in patients with reduced ejection fraction and associated coronary artery disease (CAD). We evaluated the impact of FFR on the management strategies of these patients and related outcomes. Methods and results: From 2002 to 2010, all consecutive patients with left ventricular ejection fraction (LVEF) ≤50% undergoing coronary angiography with ≥1 intermediate coronary stenosis [diameter stenosis (DS)% 50–70%] treated based on angiography (Angiography-guided group) or according to FFR (FFR-guided group) were screened for inclusion. In the FFR-guided group, 433 patients were matched with 866 contemporary patients of the Angiography-guided group. For outcome comparison, 617 control patients with LVEF >50% were included. After FFR, stenotic vessels per patient were significantly downgraded compared with the Angiography-guided group (1.43 ± 0.98 vs. 1.97 ± 0.84; P < 0.001). This was associated with lower revascularization rate (52% vs. 62%; P < 0.001) in the FFR-guided vs. the Angiography-guided group. All-cause death at 5 years of follow-up was significantly lower in the FFR-guided as compared with Angiography-guided group [22% vs. 31%. HR (95% CI) 0.64 (0.51–0.81); P < 0.001]. Similarly, rate of major adverse cardiovascular and cerebrovascular events (MACCE: composite of all-cause death, myocardial infarction, revascularization, and stroke) was significantly lower in the FFR-guided group [40% vs. 46% in the Angiography-guided group. HR (95% CI) 0.81 (0.67–0.97); P = 0.019]. Higher rates of death and MACCE were observed in patients with reduced LVEF compared with the control cohort. Conclusions: In patients with reduced LVEF and CAD, FFR-guided revascularization was associated with lower rates of death and MACCE at 5 years as compared with the Angiography-guided strategy. This beneficial impact was observed in parallel with less coronary artery bypass grafting and more patients deferred to percutaneous coronary intervention or medical therapy.